Effectiveness of Chemistry Textbooks with Problem Based Learning to Improve Students’ Learning Outcomes in Main Group Elements - Hadeli, Muhammad; Sanjaya, Sanjaya; Rachman Ibrahim, Abdul; Suharman, Andi; Ad'hiya, Eka; Kartika Sari, Diah (FKIP Universitas Lampung, 2022)
This study aims to determine the effectiveness of the main group elemental chemistry textbooks based on problem based learning in improving student learning outcomes. The design of this study was a quasi-experiment with one group pretest-posttest design. The participants in this study were sixth year chemistry education students at Universitas Sriwijaya for the 2021/2022 academic year. Test instruments was implied in this research and analyzed using statistics with N-gain data. The results showed that problem-based learning teaching materials for chemistry education students were categorized as very effective with a high level of N-gainKeywords: chemistry textbooks, problem-based learning, chemistry learning outcomes.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1376-1381